Vegetation diversity and stand carbon stocks in Wana Wisata Tampora, Situbondo, East Java - Trimanto; Lia Hapsari; Titut Yulistyarini; Sugeng Budiharta; Setyawan Agung Danarto; Shofiyatul Mas'udah; Janis Damaiyani; Rachmawan Adi Laksono; Nurlaily Lavianti; Bekti Yunanto (Jurnal Penelitian Kehutanan Wallacea, 2021)
Forest degradation and industrial development have a negative impact on the global climate. Forest vegetation plays a role in absorbing CO2 emissions in the air. The aims of this research are to determine vegetation community structure, plant diversity indices, and estimation of stands carbon stocks in Wana Wisata Tampora, Situbondo district, East Java. The research was conducted using the transect method and measured the diversity indices including Shannon-Wiener diversity index (H'), richness index (R), and evenness index (E), while the carbon stock was estimated using an allometric equation. The results showed that the diversity index value at the ground cover layer was considered high (3.18), while saplings and trees were moderate (2.68 and 2.60). The results of the stands carbon stocks estimation have shown an average value of 145.94 tonnes/ha. Plant species with high Important Value Index (IVI) and carbon contributor including Schleichera oleosa (83.97 and 56.49 ton/ha), Lannea coromandelica (58.88 and 32.35 ton/ha), Tectona grandis (24.72 and 8.5 ton/ha), Azadirachta indica (20.72 and 8.27 ton/ha), and Acacia nilotica (9.40 and 8.39). The results of the research will be useful for local governments as the basis for the development of Wana Wisata Tampora and the management of flora biodiversity